Pemberdayaan Masyarakat melalui Pelatihan Security Awarness bagi Pegawai Unit Penyelenggara Bandar Udara Ranai-Natuna - I Gusti Agung Ayu Mas Oka; M. Erawan Destyana; Yulius Bhanu (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2020)
Several cases of violations against the Limited Security Area are still frequent, showing that there is a need for efforts to increase the security of the limited security area through the addition of facilities, as well as training for personnel who handle aviation security. Therefore, the Palembang Aviation Polytechnic in collaboration with UPBU Ranai-Natuna carried out community empowerment through security awareness training for UPBU Ranai-Natuna honorary employees. The purpose of this training is that the participants are able to raise awareness of the importance of security, recognize all forms of threats and anticipate/overcome threats in the airport environment. The activity was held for 3 days, from 1 to 3 December 2020, at UPBU Ranai-Natuna, which was attended by 20 honorary UPBU Ranai-Natuna employees. The results of this activity, it can be concluded that the security awareness training went well and succeeded in achieving the training objectives, as evidenced by all the participants having passed. The results of the evaluation obtained from the questionnaire for the participants received good ratings on the instructor element, and sufficient on the service elements of the organizing committee and the training curriculum. This shows that the instructor is the main determining factor for the success of the participants in participating in the training and the quality of the organizing committee's service still needs to be improved.